2013
DOI: 10.1103/physreve.87.020701
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic crust dynamics on sand dunes

Abstract: Sand dunes are often covered by vegetation and biogenic crusts. Despite their significant role in dune stabilization, biogenic crusts have rarely been considered in studies of dune dynamics. Using a simple model, we study the existence and stability ranges of different dune-cover states along gradients of rainfall and wind power. Two ranges of alternative stable states are identified: fixed crusted dunes and fixed vegetated dunes at low wind power, and fixed vegetated dunes and active dunes at high wind power.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 31 publications
4
51
0
Order By: Relevance
“…Recent modeling studies [ Yizhaq et al , , ] have suggested the bistability of vegetation cover on sand dunes under given climatic conditions. Our recent modeling studies suggest a similar bistability for crust cover on sand dunes [ Kinast et al , ]. The field observations reported here support this prediction, as nearby plots 2 and 3 (with 1 m distance between them) on the north slope had quite different soil surface coverage, with zero crust cover for plot 2 while plot 3 had more than 40% crust cover (see Figure b).…”
Section: Discussionsupporting
confidence: 86%
“…Recent modeling studies [ Yizhaq et al , , ] have suggested the bistability of vegetation cover on sand dunes under given climatic conditions. Our recent modeling studies suggest a similar bistability for crust cover on sand dunes [ Kinast et al , ]. The field observations reported here support this prediction, as nearby plots 2 and 3 (with 1 m distance between them) on the north slope had quite different soil surface coverage, with zero crust cover for plot 2 while plot 3 had more than 40% crust cover (see Figure b).…”
Section: Discussionsupporting
confidence: 86%
“…Our model for psammophilous plants (coupled to vegetation and BSC) follows previously suggested mean field models [ Yizhaq et al , ; Kinast et al , ] for the dynamics of vegetation and BSC cover of sand dunes. The dynamical variables in our model are the fractions of regular vegetation cover, v , BSC cover, b , and psammophilous plant cover, v p , where v p is a new variable added to the model described in Kinast et al [].…”
Section: The Modelmentioning
confidence: 99%
“…Our model for psammophilous plants (coupled to vegetation and BSC) follows previously suggested mean field models [ Yizhaq et al , ; Kinast et al , ] for the dynamics of vegetation and BSC cover of sand dunes. The dynamical variables in our model are the fractions of regular vegetation cover, v , BSC cover, b , and psammophilous plant cover, v p , where v p is a new variable added to the model described in Kinast et al []. The model does not account for the geomorphology of the sand dunes and adopts a very simplified view of the various interactions involved in dune dynamics (see, for example, the much more complicated models considered in Baas and Nield [], Eastwood et al [], and references therein).…”
Section: The Modelmentioning
confidence: 99%
See 2 more Smart Citations